Implementation of electronic medical records at an Emergency Medicine Department in Tanzania: The information technology perspective - Mashoka, Ramadhani Jumanne (Afr J Emerg Med, 2019)
In 2015, the Emergency Medicine Department at Muhimbili National Hospital (MNH) installed and implemented the first Electronic Medical Record (EMR) tailored to the emergency centre (EC). The EMR deployed was designed for emergency centre use only (Emergency Department Information System (EDIS)) and linked with the existing EMR that focused on registration and billing. This very collaborative experience can be used as a reference to share the many lessons learnt by all, including hospital management, EC staff, private funders and EMR vendors. The IT Project Plan was developed to make sure steps were followed for EDIS implementation. This included the IT plan documents, specific user requirements, development of a Memorandum of Understanding and user manuals. Super key users were identified among the staff during the training and they helped to empower staff, consolidate knowledge and share the workload. Several challenges have been overcome, including when the power was not regulated so an automatic generator and uninterruptible power supply (UPS) devices installed to protect all computers. Providers were primarily a very novice group of computer users and many had little to no computer experience so were taught both basic computing skills and EDIS specific tasks. Trained staff were moved around the hospital and a lot of time was taken up training new staff, so discussion with hospital management led to retention of staff in the EC. Specific templates have been introduced to ensure adequate minimum documentation. However, even with these, clinical notes are often very brief and we are searching for further mechanisms to improve this. Hospitals in low-resource settings considering the implementation of an EMR should ensure that a comprehensive plan is in place that involves significant staff training, improvement of existing, or installation of new information technology systems, ongoing ICT support and funds for unforeseen issues and ongoing maintenance.